CALCULATE METHOD OF THE TWILIGHT SKY BRIGHTNESS IN THE SOLAR VERTICAL, STIPULATED BY A MULTIPLE SCATTERING OF A SUNLIGHT - Shakun, L. S.; Motrich, V. D.; Melykjants, S. M. (Одеські астрономічні публікації, 2017)
Use of a twilight sounding method of the Earth's atmosphere with the aim to reveal aerosols inflow to the upper and medial atmosphere needs a method of separation twilight sky brightness to the brightness of primary and secondary twilight. Method of secondary twilight brightness calculation on a declination of the logarithm of twilight sky brightness caused by a multiple scattering of sunlight is discussed. The calculation procedure of a declination of the logarithm of secondary twilight brightness on observations in solar vertical is given. The use equal declination of the logarithm of secondary twilight brightness for all viewing directions in solar vertical is proved.